Critical inputs to the integrated solid waste management framework plan of Iloilo City policy, social and management/technology perspectives and recommendations - Octavio, Ma. Cristina V.
This paper is a special problem on the lack of a solid waste management plan in Iloilo City and is basically a collaboartion on critical inputs from solid waste management's policy, social, and management / technology perspectives.